Green Constitution Model in Civic Education Learning to Develop Students' Civic Engagement (Comparative Study in 12 High Schools, 5 Vocational High Schools, 7 Vocational High Schools Bandung) - Fanny Dwi Octaviany; Kokom Komalasari; Susan Fitriasari (Journal of International Conference Proceedings (JICP), 2020)
Environmental damage must be considered from a small scope but has a large influence, can be applied through the Green Constitution to develop students' Civic Engagement. The appropriate method used in this research is a comparative study with a qualitative approach, which will be applied with a minimum of 3 schools in Bandung. The results showed; How is the implementation of the Green Constitution model in Civic Education learning to develop Civic Engagement for students. After doing research, this model was successful despite experiencing differences in the results of each school, this success was due to the use of the Green Constitution model through the citizen project.